زوجین کے تنازعات اور ان کے بچوں پر منفی اثرات: قرآن و سنت کی روشنی میں حل: Marital Disputes & Their Negative Effects on Children: Solutions In The Light of the Qur’an & Sunnah - Dr. Shazia; Noor Ul Ain (Al-Amīr Research Journal for Islamic Studies, 2025)
The marital relationship between spouses (husband and wife) serves as the foundation for family structure and stability. In the light of the Qur’an and Sunnah, spouses are regarded as a source of support and tranquility for one another. However, when conflicts and disputes arise between them, they disrupt domestic harmony and significantly impact the psychological, moral, and religious upbringing of children. Such disputes often result in fear, insecurity, lack of confidence, and aggressive behaviors among children, which in turn affect their academic performance, ethical values, and spiritual orientation. Islam places responsibility upon parents to guide their families with patience, wisdom, piety, and good character so that the home may become a center of love and peace, providing children with proper training and a positive moral environment. Thus, the conduct of parents not only strengthens the marital bond but also plays a vital role in shaping the personality, ethics, and religious consciousness of their children. Keywords: Spouses, Marital conflicts, Domestic harmony, Child upbringing, Psychological impacts, Moral impacts, Religious impacts, Qur’an and Hadith, Patience and tolerance.